DESA DALAM MENGELOLA ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) UNTUK PEMBANGUNAN - Ahmad Syafii; Kismartini Kismartini (Journal of Public Policy and Management Review, 2020)
The lateness of Kumendung village in sending draft of village regulation about Village Revenue and Expenditure Budget and the report of the realization about implementation of the Village Revenue and Expenditure Budget are the background in this study. The purpose of this study is to analyze the management of Village Revenue and Expenditure Budget in Kumendung village. In addition, it also to analyze the supporting and the inhibiting factors in managing the Village Revenue and Expenditure Budget in Kumendung village. The method used is a qualitative research method with descriptive approach. The results showed that planning, implementation, administration, reporting, and accountability of Village Revenue and Expenditure Budgets were not running well. Mainly in the administration, reporting, and accountability activities which are often delayed. The inhibiting factors in the management of Village Revenue and Expenditure Budget in Kumendung village is the inaccurate supervision by the Head Village of Kumendung village, and the low coordination between village government and village institutions. While the supporting factor is the good communication in the village government and the effective leadership style of the Head Village of Kumendung village. The recommendation which given are the need for change of focus in controlling by the Head Village of Kumendung village, improvement of the coordination system, and giving more intensive coaching and assistance to village official.